Women's Studies in the 1990s
IX, 182 p.
Keywords: This interdisciplinary collection is concerned with important theoretical and methodological issues facing women's studies. Drawing on feminist theory and politics it addresses a range of questions raised for women's studies by work conducted in history, literature, politics and sociology. The editors provide a context for these debates in their introductory essay which gives an overview of the development of women's studies and reflects on its current position. In their concluding chapter they also suggest a framework from which women's studies might move forward.